2019
DOI: 10.1007/978-3-030-24766-9_1
|View full text |Cite
|
Sign up to set email alerts
|

Succinct Data Structures for Families of Interval Graphs

Abstract: We consider the problem of designing succinct data structures for interval graphs with n vertices while supporting degree, adjacency, neighborhood and shortest path queries in optimal time in the Θ(log n)bit 1 word RAM model. The degree query reports the number of incident edges to a given vertex in constant time, the adjacency query returns true if there is an edge between two vertices in constant time, the neighborhood query reports the set of all adjacent vertices in time proportional to the degree of the q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 35 publications
(48 reference statements)
0
19
0
Order By: Relevance
“…To illustrate this further, there already exists a large body of work on representing various combinatorial objects succinctly. A partial list of such combinatorial objects would be trees [18,21], various special graph classes like planar graphs [2], chordal graphs [19], partial k-trees [11], interval graphs [1] along with arbitrary general graphs [12], permutations [17], functions [17], bitvectors [22] among many others. We refer the reader to the recent book by Navarro [20] for a comprehensive treatment of this field.…”
Section: Related Workmentioning
confidence: 99%
“…To illustrate this further, there already exists a large body of work on representing various combinatorial objects succinctly. A partial list of such combinatorial objects would be trees [18,21], various special graph classes like planar graphs [2], chordal graphs [19], partial k-trees [11], interval graphs [1] along with arbitrary general graphs [12], permutations [17], functions [17], bitvectors [22] among many others. We refer the reader to the recent book by Navarro [20] for a comprehensive treatment of this field.…”
Section: Related Workmentioning
confidence: 99%
“…Recently such results have appeared in literature for intersection graphs like interval graphs [2] and chordal graphs [8]. For interval graphs, [2] gives an n log n + O(n) bit succinct data structure that supports degree and adjacency queries in O(1) time while neighborhood query for vertex a in O(d) time where d is the degree of the vertex a. In the case of chordal graphs, [8] gives an n 2 /4 + o(n) bit succinct data structure that supports adjacency query in f (n) time where f (n) ∈ ω(1), degree of a vertex in O(1) time and neighborhood in (f (n)) 2 time per neighbour.…”
Section: Introductionmentioning
confidence: 96%
“…Formally, given a set T consisting of combinatorial objects with certain property, our goal is to store any arbitrary member x ∈ T using the information theoretic minimum of log(|T |) + o(log(|T |)) bits (throughout this paper, log denotes the logarithm to the base 2) while still being able to support the queries efficiently on x. Recently Acan et al [2] showed that the information-theoretic lower bound for representing interval graphs with n vertices is at least n log n bits, and as path graphs are a proper superclass of interval graphs, this lower bound also holds true for path graphs. Surprisingly, we manage to construct an n log n + o(n log n)-bit data structure for representing path graphs matching this information-theoretic lower bound, thus, obtaining succinct data structure for path graphs for the first time in literature.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations